MANAGEMENT SYSTEM OF INNOVATIVE ACTIVITY DEVELOPMENT IN THE REPUBLIC OF KAZAKHSTAN - S.R. Abzhalelova; K.M. Zhumaxanova; A.Zh. Abdrakhmanova (Academic Journal of Physical and Chemical Sciences, 2019)
The purpose of the work is to determine the most effective existing system of innovation management in the country. To conduct the work, comparison methods, analysis and synthesis were used, with the help of which the world experience of creating an innovation process management system is presented. In the modern economy, the development, implementation and use of innovations allows the country to be competitive, create jobs and increase the welfare of the population. The results of the work are a characteristic of an effective system of innovation management at the state level. The area of application of the results is in the practical activities of the state and is reflected in the results of the implementation of state programs and regulatory legal acts in the field of innovation. As a result of the analysis of the world and Kazakhstani experience in creating a management system for innovation, conclusions were drawn about the need for systematic and focused work at all levels. Consistency implies a concentration of activities and an emphasis on priorities in the development and application of innovations. Innovations should be developed in such areas as public services, information technology, medicine, tourism, finance and other important areas.